A design evaluation of Golden Acres, an institution for the elderly - Espino, Eleanor Mendoza; Mayo Adelaida V. (1998.)
The focus of this study is Golden Acres, a home for the aged, a government institution run by the Department of Social Welfare and Development (DSWD). It is a temporary home to more than 200 homeless Filipino males and females aged 60 and above. The researcher's objective is to find the appropriate design for Golden Acres, particularly the bedroom, dining and living area, that will be conducive to the occupants' safety, security, comfort and access, considering their limitations and impairments as a consequence of aging. The methodology employed by the researcher is the case study method. The findings revealed that due to the limited budget of DSWD for redesigning Golden Acres' cottages', specifically Sta. Rita Cottage, existing layout, furniture, and facilities will be retained. For practicality, the furnishings will still be used except for some which have to be improved and some which need to be changed to achieve better compatibility of the human body with the furniture. To help the occupants achieve a certain degree of independence in their activities and movements, the interior is designed to promote ease of circulation and simple traffic patterns, resulting in occupants' safety, comfort and convenience. Adoption of a brighter color scheme, like using red-orange with compliments of turquoise or blue for the dwelling unit, is recommended to avoid the traditional institutional look and to attain a brighter, healthier and livelier environment. Specifically with reference to lighting, provisions of flourescent lighting is used for the illumination of the general space and for decorative lighting. Lighting, in general should be intensified but without glare. Windows are also used to be a source of light. Windows will also provide ventilation to be augmented by electric fans. The floor materials are non-slip and non-stain, in which the use of pattern and colored unglazed tiles is suggested. The tiles will also provide visual guides easily perceived by the elderly with declining vision and for aesthetic purposes. All the spaces are designed to provide easy access to bathrooms and hallways. Lastly, spatial scale consideration is recommended in which small spaces are maintained to provide privacy for the occupants to make conversation easier and reduce confusion.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Older people -- Housing -- Philippines -- Designs and plans -- Evaluation; Old age homes -- Philippines -- Designs and plans -- Evaluation; Golden Acres